Wake control of a circular cylinder with rotating rods: Numerical simulations for inviscid and viscous flows. (October 2021) - Carvalho, I.A.; Assi, G.R.S.; Orselli, R.M.
Abstract: This paper investigates the suppression of vortex shedding of a system comprised of a main circular cylinder surrounded by eight small rotating rods. Numerical simulations for an inviscid flow and a viscous flow at a Reynolds number of 100 have been performed. The rotation of each rod was controlled to promote the injection of momentum into the boundary layer and to mitigate the formation of vortices in the wake. Two cases have been investigated regarding the rotation speeds: case 0, in which all rods rotated at the same rate; and case 1, in which the rotation speeds were inspired by the potential-flow velocity field around a bare cylinder. Results showed that given enough rotation speed, both cases completely suppressed the formation of vortices, reducing the mean drag coefficient below that of a bare cylinder and mitigating fluctuating lift. Case 1 was the most efficient in reducing drag. Considering the system's total power loss, there is a range of rotation speeds capable of reducing the overall drag with minimum power spent to rotate the rods. It is worth noting that simulations with the inviscid flow captured an inversion of lift acting on the rotating rods that has not been verified to occur for the viscous flow. Graphical abstract: